The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3174/ajnr.a3104
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Hypervascular and Hypovascular Metastases and Normal Bone Marrow of the Spine Using Dynamic Contrast-Enhanced MR Imaging

Abstract: BACKGROUND AND PURPOSE:The role of DCE-MR imaging in the study of bone marrow perfusion is only partially developed, though potential applications for routine use in the clinical setting are beginning to be described. We hypothesize that DCE-MR imaging can be used to discriminate between hypervascular and hypovascular metastases based on measured perfusion variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 32 publications
(49 reference statements)
2
29
0
Order By: Relevance
“…Although diffusionweighted imaging and dynamic-enhanced T1-weighted imaging were reported to be useful for the differential diagnosis of spinal lesions [27][28][29], some contraindications and a high expense may limit a clinical use of MRI. At present, ssDECT is not suitable as a modality of first choice for the diagnosis of vertebral metastases due to the need of radiation exposure and special equipment.…”
Section: Discussionmentioning
confidence: 97%
“…Although diffusionweighted imaging and dynamic-enhanced T1-weighted imaging were reported to be useful for the differential diagnosis of spinal lesions [27][28][29], some contraindications and a high expense may limit a clinical use of MRI. At present, ssDECT is not suitable as a modality of first choice for the diagnosis of vertebral metastases due to the need of radiation exposure and special equipment.…”
Section: Discussionmentioning
confidence: 97%
“…These quantitative parameters have demonstrated their value in detecting the differences in microvascular environment among metastatic lesions before and after treatment 9 , benign and pathological fractures 10 , and hypovascular and hypervascular lesions. 11,12 Vertebral metastases demonstrate very different histological patterns depending on the primary tumor. There is, however, a common feature in all of them: neoangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…17 In particular, DCE-MRI’s ability to distinguish between benign and malignant marrow lesions of the vertebral and appendicular skeleton is notable. 1821 Furthermore, perfusion imaging has been shown to be adept in monitoring the response to radiotherapy of tumors in spinal bone metastases. 22 A recent study has shown that the semi-quantitative metrics extracted from DCE-MRI can differentiate between hypervascular and hypovascular metastatic lesions of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…22 A recent study has shown that the semi-quantitative metrics extracted from DCE-MRI can differentiate between hypervascular and hypovascular metastatic lesions of the spine. 18 Our aim in this study was to evaluate spinal metastases from RCC and PC using the T1 DCE-MRI perfusion technique and to assess the sensitivity and specificity of perfusion parameters obtained by both quantitative (derived from pharmacokinetic modeling) and semi-quantitative methods, which would allow for noninvasive discrimination between hypovascular and hypervascular spinal metastases. We hypothesized that the values for perfusion parameters will be higher for metastases originating from RCC than from PC, given that the primary source of metastatic RCC lesions confers a hypervascular pattern.…”
Section: Introductionmentioning
confidence: 99%